Efficacy of risk stratification protocols and clinical, physical, and biochemical parameters to previse signals and symptoms during cardiovascular rehabilitation programs: Protocol for an observational trial - Vanzella, Laís Manata [UNESP]; Takahashi, Carolina [UNESP]; Ribeiro, Felipe [UNESP]; Lima, Isabelle Maina [UNESP]; Silva, Anne Kastelianne França Da [UNESP]; Christófaro, Diego Giulliano Destro [UNESP]; Vanderlei, Luiz Carlos Marques [UNESP] (Wolters Kluwer, 2019)
IntroductionDespite the benefits, cardiovascular rehabilitation programs (CRPs) have been related to the appearance of signals and symptoms. Risk stratification protocols are commonly used to identify risks during the physical exercise; however, studies that investigate their efficacy to previse signals and symptoms are inconclusive. Furthermore, clinical, physical, and biochemical parameters have been used as risk markers for the appearance of adverse events, and to investigate their efficacy to previse signals and symptoms during the CRP sessions that could better guide the strategies adopted on these programs.ObjectivesThe aim of this study was to evaluate the correlations between risk stratification protocols and clinical, physical, and biochemical parameters with the appearance of signals/symptoms during CRP, as well as to evaluate if modifications on clinical, physical, and biochemical parameters could influence in the appearance of signals/symptoms during CRP.Materials and methodsThe study was prospectively registered at ClinicalTrials.gov (NCT03446742). Forty-four patient participants of a CRP will be evaluated. First, their risk stratification is going to be performed by 2 evaluators and their clinical, physical, and biochemical parameters are going to be measured. Then, the patients are going to be followed during 24 sessions during their CRP routines in order to identify appearance of their signals/symptoms. So, the patients are going to perform their cardiovascular rehabilitation routines for 6 months and then, their clinical, physical, and biochemical parameters are going to be measured again and they are going to be followed during 24 sessions during their CRP routines in order to identify the appearance of their signals/symptoms.
Keywords: autonomic modulation; blood pressure; cytokines; exercise; heart rate; inflammation; muscle strength; rehabilitation services; risk; signals and symptoms